Influence of the 3D Printing Fabrication Parameters on the Tensile Properties of Carbon-Based Composite Filament - Prodromos Minaoglou; Anastasios Tzotzis; Nikolaos Efkolidis; Panagiotis Kyratsis (Applied Mechanics, 2024)
In this study, the effect of certain 3D printing conditions on the tensile strength of 3D-printed specimens was investigated. The printing material was CARBON: PLUS (NEEMA3D™, Athens, Greece), which consists of Polyethylene Terephthalate Glycol (PET-G) reinforced with 20% carbon fiber. All samples were printed with a closed-type, large-format Fused Filament Fabrication (FFF) 3D printer. Before printing the samples, three parameters related to the 3D printing settings were selected in order to vary their values (flow = the flow of the material, wall = the total thickness of the wall, and layer = the thickness of the print layer). Each parameter was given three different values for experimentation. In this study, all 27 possible combinations of variable parameters were fabricated. Each experiment was repeated twice, and from the test results, the maximum tensile strength was obtained for each specimen separately. From the results of the measurements, the most critical parameter appeared to be the height of the layer. The other two variable parameters, the flow and wall, locally affected the strength of the specimens. Later, an empirical model was developed according to the full factorial design for each combination of values. Finally, the R-sq (pred) value achieved was equal to 97.02%, and together with the residual analysis performed, the accuracy of the proposed maximum tensile strength mathematical model was proven.